Post electoral crisis and international remittances: Evidence from Côte d'Ivoire - Yao Silvère Konan (Kiel Institute for the World Economy (IfW), 2017)
This paper analyzes the determinants of international remittances received during the post electoral crisis in Côte d'Ivoire, using data collected 5 months after the end of the conflict. The author finds that the crisis has been a means of mobilizing social capital and demonstrating altruistic and insurance behaviors beyond the bounds of kinship. Transfers are mainly sent for consumption purpose, but amounts transferred for small investments and human capital are higher. Moreover, the propensity to transfer higher amounts decreases when emigration occurred after the November 2004 violent events. Altruism resists to time.
Keywords: F22; F24; O15; 330; remittances; Côte d'Ivoire; post electoral conflict; Sub-Saharan Africa; migration